2003
DOI: 10.1007/s00380-003-0699-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac hemangioma: a report of two cases and review of the literature

Abstract: Cardiac hemangioma is extremely rare. We encountered two patients with cardiac hemangioma detected by thoracic echocardiography during a medical checkup. In the first case, transthoracic echocardiography revealed a pedunculated tumor in the left ventricle. Selective left coronary angiography demonstrated that the main feeding artery of the tumor arose from the third diagonal branch of the left anterior descending coronary artery. In the second case, thoracic and transesophageal echocardiography showed an oval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
53
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 15 publications
0
53
0
6
Order By: Relevance
“…Differentiation from malignant tumors, which mainly appear in the right atrium, is very important [6]. In our case the tumor was attached to the interatrial septum, a common location for myxoma [7].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Differentiation from malignant tumors, which mainly appear in the right atrium, is very important [6]. In our case the tumor was attached to the interatrial septum, a common location for myxoma [7].…”
Section: Discussionmentioning
confidence: 74%
“…The left atrium is the predominant location for cardiac tumors (72%) [6]. However, according to a review of 56 cases, only 7% of cardiac hemangiomas occur in that chamber, whereas the majority of cardiac hemangiomas tend to arise from the right ventricle (36%), left ventricle (34%), and right atrium (23%) [7]. Differentiation from malignant tumors, which mainly appear in the right atrium, is very important [6].…”
Section: Discussionmentioning
confidence: 99%
“…Kojima et al 2 evaluated 56 patients with cardiac hemangiomas, and most frequently observed these tumors in the cardiac ventricle (right ventricle, 35 %; left ventricle, 34 %), followed in order by the right atrium (23 %), interatrial septum (11 %), interventricular septum (11 %), and left atrium (7 %). Different clinical symptoms such as chest congestion, polypnea, cardiac failure, pericardial effusion, and arrhythmia were occurred due to the different sites results in cardiac hemangiomas.…”
Section: Discussionmentioning
confidence: 99%
“…По данным литературы единое мнение по первой дате описания гемангиомы сердца отсутствует, но прео-бладающее большинство клиницистов считают, что это произошло в 1893г [5][6][7][8]. В последующем, вплоть до настоящего времени, в отечественных и преимуще-ственно зарубежных работах излагаются, как правило, единичные наблюдения по рассматриваемой патоло-гии.…”
Section: Discussionunclassified
“…Среди морфологического многообразия послед-них гемангиомы сердца встречаются чрезвычайно редко. Их частота составляет только 0,45-2,8% всех первичных опухолей сердца [2][3][4][5][6]. В нашем Центре за период с декабря 1962г по декабрь 2014г были выпол-нены хирургические вмешательства 283 больным с новообразованиями сердца, 263 (92,9%) из которых страдали морфологически верифицированными добро-качественными и 20 (7,1%) -злокачественными опухо-лями.…”
unclassified